2011
DOI: 10.1371/journal.pgen.1001307
|View full text |Cite
|
Sign up to set email alerts
|

Association between Common Variation at the FTO Locus and Changes in Body Mass Index from Infancy to Late Childhood: The Complex Nature of Genetic Association through Growth and Development

Abstract: An age-dependent association between variation at the FTO locus and BMI in children has been suggested. We meta-analyzed associations between the FTO locus (rs9939609) and BMI in samples, aged from early infancy to 13 years, from 8 cohorts of European ancestry. We found a positive association between additional minor (A) alleles and BMI from 5.5 years onwards, but an inverse association below age 2.5 years. Modelling median BMI curves for each genotype using the LMS method, we found that carriers of minor alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
177
2
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(214 citation statements)
references
References 60 publications
33
177
2
2
Order By: Relevance
“…Although just one study found an association with obesity in this review, there are in previous studies a description of decreased response to satiety in children and adolescents when rs9939609 is present, confirmed in other studies [25][26][27][28] . As Cecil, Frayling et al also identified, rs9939609 carries an association with a higher Body Mass Index (BMI) in children and adults 29 .…”
Section: Discussionsupporting
confidence: 75%
“…Although just one study found an association with obesity in this review, there are in previous studies a description of decreased response to satiety in children and adolescents when rs9939609 is present, confirmed in other studies [25][26][27][28] . As Cecil, Frayling et al also identified, rs9939609 carries an association with a higher Body Mass Index (BMI) in children and adults 29 .…”
Section: Discussionsupporting
confidence: 75%
“…Reports confi rm the role of FTO rs9939609, and surrogates for this variant, on BMI and fat mass in children and adolescents from Caucasian and non-Caucasian populations (Cecil et al, 2008;Fang et Xi et al, 2010). Additionally, several studies have confi rmed an increasing association between rs9939609 and BMI from early childhood to adolescence (Hardy et al, 2010;Haworth et al, 2008b;Rzehak et al, 2010;Sovio et al, 2011). Sovio and colleagues, in their meta-analysis of European children (8 cohorts, infants to 13 year olds) found that the minor (A) allele of the rs9939609 was additively associated with increasing BMI as early as 5.5 years onwards, and interestingly an inverse association was found below the age of 2.5 years (Sovio et al, 2011), supporting what is known about the timing of adiposity rebound and risk of adult obesity (Whitaker et al, 1998) and the interplay between behaviour (appetite, physical activity) and environment with age Wright et al, 2011).…”
Section: Fat Mass and Obesity Associated Gene -A Role In Common Obesitymentioning
confidence: 93%
“…Additionally, several studies have confi rmed an increasing association between rs9939609 and BMI from early childhood to adolescence (Hardy et al, 2010;Haworth et al, 2008b;Rzehak et al, 2010;Sovio et al, 2011). Sovio and colleagues, in their meta-analysis of European children (8 cohorts, infants to 13 year olds) found that the minor (A) allele of the rs9939609 was additively associated with increasing BMI as early as 5.5 years onwards, and interestingly an inverse association was found below the age of 2.5 years (Sovio et al, 2011), supporting what is known about the timing of adiposity rebound and risk of adult obesity (Whitaker et al, 1998) and the interplay between behaviour (appetite, physical activity) and environment with age Wright et al, 2011). A temporal dip in the effect of FTO rs9939609 on BMI in children is proposed at the mid-pubertal age of around 13-14 years which may be linked to alterations in physiologic and endocrine factors that trigger puberty (Rutters et al, 2011).…”
Section: Fat Mass and Obesity Associated Gene -A Role In Common Obesitymentioning
confidence: 99%
“…We weighted the SNPs in the GRS based on the effect estimates from the GWAS in adults. Effect sizes of individual SNPs may vary across the life course and adult weights may not appropriately cover the true effect sizes in children (27). There is a small GWAS available in children, but for proper estimation of the appropriate weights in children, there is a need for large meta-analyses of GWASs in children on lipid phenotypes (11).…”
Section: Associations Of Snps For Hdl-c With Childhood Lipid Levelsmentioning
confidence: 99%